1993
DOI: 10.1111/j.1748-1716.1993.tb09472.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of regional myocardial performance caused by blood withdrawal and infusion in acute ischaemic canine heart

Abstract: The effect of changes in preload on regional myocardial motion in acute ischaemia was examined by miniature ultrasonic gauges after left anterior descending coronary artery occlusion in eight open chest dogs with the pericardium preserved. Left ventricular end-diastolic pressure was varied by blood withdrawal and infusion. When preload changed, isovolumetric shortening in the non-ischaemic region was inversely related to that in the ischaemic region. When preload decreased, stroke volume decreased and was acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(13 reference statements)
0
6
1
Order By: Relevance
“…These results seem to differ from those of the previous reports (Akaishi et al 1985;Noma et al 1988a, b;Ishikawa et al 1993;Sakuma et al 1993) which showed that the increase of the isovolumetric shortening in the non-ischemic region reflected the increase of the isovolumetric bulging in the ischemic region, both in the preload change and in the afterload change. The changes of the end-diastolic relations between the non-ischemic and ischemic regions partly affected the relationship between these two regions in the isovolumetric phase.…”
Section: Regional Wall Motion In the Isovolumetric Phasecontrasting
confidence: 56%
See 4 more Smart Citations
“…These results seem to differ from those of the previous reports (Akaishi et al 1985;Noma et al 1988a, b;Ishikawa et al 1993;Sakuma et al 1993) which showed that the increase of the isovolumetric shortening in the non-ischemic region reflected the increase of the isovolumetric bulging in the ischemic region, both in the preload change and in the afterload change. The changes of the end-diastolic relations between the non-ischemic and ischemic regions partly affected the relationship between these two regions in the isovolumetric phase.…”
Section: Regional Wall Motion In the Isovolumetric Phasecontrasting
confidence: 56%
“…The period from end-diastole to aortic valve opening was determined as the isovolumic contraction phase, and the period from aortic valve opening to end-systole as the ejection phase. For comparison of the segment lengths in the ischemic and the non-ischemic regions, each measured value was normalized with the end-diastolic length of control being 10 mm (Shirato et al 1978;Ishikawa et al 1993). Total systolic shortening equals end-diastolic length minus end-systolic length.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations